ON KNOWLEDGE SYSTEM FORMATION IN INTELLIGENT ELECTRONIC DOCUMENTATION OF MECHATRONIC OBJECTS - Andrey K. Tugengold; Alexander S. Tishin; Alexey F. Lysenko (Вестник Донского государственного технического университета, 2018)
The recommendations on building the knowledge system based on the conceptual approach to the mechatronic technological object documentation are made. The example of the intelligent management application for the improvement in the machine part cutting accuracy is considered.